2007
DOI: 10.1016/j.ejpain.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

A minimal stress model for the assessment of electroacupuncture analgesia in rats under halothane

Abstract: The use of anesthetics in acupuncture analgesia is controversial. We evaluate a steady-state light anesthesia model to test whether minimal stress manipulation and reliable measurement of analgesia could be simultaneously achieved during electroacupuncture (EA) in animals. A series of experiments were performed. Firstly, EA compliance and tail-flick latencies (TFL) were compared in rats under 0.1%, 0.3%, 0.5%, 0.7%, or 1.1% halothane for 120min. Under 0.5% halothane, TFL were then measured in groups receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 44 publications
6
41
1
Order By: Relevance
“…However, in the present study, electroacupuncture treatment at BL60 acupoint reduced the number of c-Fos positive neurons in not only superficial layer laminae I-II but also in deep layer laminae III–VI of the spinal cord at the L4-5 level, compared to a formalin injection only group. This result is consistent with other studies which observed a reduction of c-Fos expression in both superficial and deep layers of the spinal cord dorsal horn in the electroacupuncture-treated groups of a carrageenan-induced pain rat model [16, 36] and a formalin model [17]. Furthermore, it is considered that the mechanism of pain suppression by electroacupuncture at BL-60 acupoint is due to its action at the spinal cord level, but not at the supra-spinal level.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in the present study, electroacupuncture treatment at BL60 acupoint reduced the number of c-Fos positive neurons in not only superficial layer laminae I-II but also in deep layer laminae III–VI of the spinal cord at the L4-5 level, compared to a formalin injection only group. This result is consistent with other studies which observed a reduction of c-Fos expression in both superficial and deep layers of the spinal cord dorsal horn in the electroacupuncture-treated groups of a carrageenan-induced pain rat model [16, 36] and a formalin model [17]. Furthermore, it is considered that the mechanism of pain suppression by electroacupuncture at BL-60 acupoint is due to its action at the spinal cord level, but not at the supra-spinal level.…”
Section: Discussionsupporting
confidence: 93%
“…There have been numerous studies that observed the pain-relieving effects of acupuncture [13, 16, 17, 2325]. To our knowledge, however, there are no reports except for Kim et al [26] and Zou et al [27] to study the pain-relieving effects of acupuncture at the BL60 acupoint.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the withdrawal thresholds to MS in the incised and nonincised paws of sham EA rats treated with saline or amitriptyline also did not change throughout the post-incision period of observation. We can conclude that isoflurane anesthesia is unlikely to interfere with the EA-induced increase in TFL or reduction in incision hyperalgesia, as proposed elsewhere (Wen et al, 2007).…”
Section: Discussionmentioning
confidence: 73%
“…Procedures were conducted in rats anesthetized with isoflurane (in oxygen flow; 2% for induction, and 0.5% for maintenance) to minimize the stress induced by the animal restraint that is necessary for needle insertion and stimulation (Wen et al, 2007). Stainless steel acupuncture needles (0.18 mm× 8 mm) were inserted at a depth of 5 mm into each hind leg at the acupoints Zusanli and Sanyinjiao.…”
Section: Electroacupuncturementioning
confidence: 99%